0021 The effect of video gaming on the sleep patterns and well-being of U.S. Marines. (25th May 2022) - Matsangas, Panagiotis; Shattuck, Nita; Shattuck, Lawrence; Xu, Jason; Orpilla, Edrie; Lawrence-Sidebottom, Darian; Dotson, Elizabeth; Bowen, Zena
Abstract: Introduction: Video gaming (VGs) is a popular activity among active-duty service members (ADSMs) and can have both positive and negative impacts on ADSM well-being and behavior. The overall aim of the project was to assess attributes and aspects of video gaming in the United States Navy and Marine Corps (USMC). Our current results specifically address the effects of video gaming on the sleep patterns of Marines. Methods: Data were collected from 927 Marines from three USMC commands. Volunteers completed a survey and participated in semi-structured focus groups. The survey items focused on demographic and occupational characteristics, behavioral habits, video gaming habits, why ADSMs play video games, and functional effects. Validated tools were used to assess depression (Patient Health Questionnaire-8), generalized anxiety (GAD-7), excessive daytime sleepiness (Epworth Sleepiness Scale), and drinking habits (Alcohol Use Disorders Identification Test for Consumption-AUDIT-C). Results: The study sample included predominantly males (854, 92.3%) and enlisted personnel (771, 83.3%). Also, 850 (91.7%) Marines reported playing video games (799 [94.0%] males). Gamers reported playing VGs predominantly later in the day (i.e., after work and before bedtime). Approximately 16% of gamers reported sleeping later because of playing VGs when at home/off duty, 14% when on duty/in port, and 5% when deployed/underway. When deployed/underway, most gamers reported playing video games in their racks (93.2%). Gamers reported symptoms of depression ( 23% of ADSMs), generalized anxiety ( 19%), excessive daytime sleepiness ( 33%), and AUDIT-C scores suggestive of heavy drinking (39%). Excessive gamers tended to be younger, used dysfunctional coping styles more frequently, and played VGs more frequently and for more hours. Excessive gamers were more likely to report sleeping later because of playing VGs and to be identified with symptoms of depression, anxiety, and excessive daytime sleepiness. Conclusion: This study provided valuable insight into how video gaming habits affect ADSM sleep patterns. Further research is needed to objectively assess the relationship between video gaming and sleep in operational conditions. Support (If Any): Supported by the Manpower and Reserve Affairs (M&RA), Headquarters Marine Corps (HQMC), and the Office of the Chief of Naval Operations/21st Century Sailor Office (OPNAV/N17).